Placer gold in the Cretaceous Blue Spur Conglomerate at Waitahuna, southern New Zealand. Issue 3 (3rd July 2017) - Malloch, Kirstine; Kerr, Gemma; Craw, Dave
ABSTRACT: Blue Spur Conglomerate is a Cretaceous paleoplacer gold deposit that yielded abundant gold in the 19th century Otago gold rush. A modern gold mine near Waitahuna in southeast Otago has provided new insights into the nature of the conglomerate and a window into some technical, logistical and environmental challenges that faced the historical miners. Most of the clasts in the conglomerate were eroded from fresh basement along the Tuapeka Fault Zone, with derivation from the north or northeast. There are three principal gold morphological groups in the conglomerate: angular nuggety gold (up to 15 mm), commonly intergrown with quartz; rounded ellipsoidal particles (10–500 µm); and extensively flattened and folded flakes (10–500 µm). Most of that gold was derived from nearby basement sources in the Otago Schist. Diagenetic alteration of the conglomerate and subsequent weathering has resulted in enhanced clay contents and friability of the conglomerate clasts, which contributed to elevated suspended sediment loads in mine-processing waters.